Sonate pastorale, dediée à Mons: Noble de Sonnenfels ; composee par L. van Beethoven, op. 28 - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Czerny, Carl, 1791-1857 (editor):::Contributor::::::::::::; Richards, Brinley, 1819-1885 (editor):::Contributor:::::::::::: (United Kingdom; R. Cocks & Co.; London, 2022)
Mid-nineteenth century edition of the Sonata no. 15 in D Major, op. 28, edited by Carl Czerny and published by R. Cocks in London in the series "Beethoven's Masterpieces"; variant issue printed from the same plates but with fingerings added and additional pagination 66-87; printed at foot of p. 1: "Classical Pianist No. 5, Brinley Richards." Includes metronome markings.